Is it the Gums, Teeth or the Bite? Effectiveness of Dimensions of Enforcement in Curbing Corruption - Salvatore Capasso; Rajeev K. Goel; James W. Saunoris (Center for Economic Studies and ifo Institute (CESifo), 2018)
Adding a new dimension to determinants of corruption, this paper examines the effectiveness of enforcement in reducing corruption. We compare the influences of latent enforcement (police, judicial, and prosecutorial employment) versus actual enforcement (conviction rates) and enforcing institutions. Results based on data for more than 80 countries show that piecemeal enforcement to combat corruption by increasing enforcement employment is ineffective, rather comprehensive improvements in institutions by strengthening the rule of law or regulatory quality bear greater results. Thus, when it comes to corruption control, strong gums (institutions) are more effective than showing teeth (enforcement employment) or the bite (conviction rates).
Keywords: K42; F50; 330; corruption; enforcement; conviction rate; police; judges; prosecutors; institutions; regulatory quality; rule of law